The role of online shopping for consumers in South Africa - Pereira Soares Moreno, Arif (My University, 2017)
ABSTRACT The South African retail landscape is changing and the role of online shopping has impacted the manner in which traditional brick and mortar retailers conduct business. The purpose of this research was to evaluate the factors contributing to the use of online shopping for consumers in South Africa. This paper investigated the perceptions of a sample, using a quantitative approach, of both genders and a diverse age range. A sample of 204 respondents was sent a link to a web-based survey questionnaire which asked a series of questions relating to the ability to shop online. The data was analysed using the statistical software package SPSS. A factor analysis was used to determine the factors which contributed towards online shopping where a correlation matrix was used that identified the relationship between these factors. The overall conclusion was that two research questions were put forward by the researcher, namely; the factors which contribute the most to online shopping, and, the factors which contribute the least to online shopping. Given that the role of the traditional in-store retail business model is being disrupted by the advent of the internet and technological advancements, retailers need to think differently on how they will get consumers to purchase their products. The shift of consumer needs, behaviours and purchasing habits further reveal the complex environment in which retailers operate. This research provides guidance to retailers in understanding the factors that contribute to the use of online shopping for consumers. These findings assist retailers in understanding the elements that enhance an online experience for consumers, and understand the extent to which online is impacting traditional shopping.
M.B.A. Thesis
Keywords: Teleshopping, Internet marketing, Consumer behavior -- South Africa.